Enhancing MSME Market Access Through Financial Literacy and Digital Technology: Insights from Tojo Una-Una - Putri Reski Amalia; Badjeber, Fadli Hadi; Mardiyah; Irham Pakkawaru (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2025)
MSMEs in Tojo Una-Una Regency face constraints such as low financial literacy, limited use of digitalization, and a lack of business presentation strategies. This impacts limited market access and difficulty in obtaining funding. This community service program aims to increase the capacity of MSMEs thru financial literacy training, QRIS utilization, and pitch deck preparation. The method used is a participatory-educational approach that actively involves MSME actors. The activity stages include initial observation, interactive material delivery on product cost of goods sold (COGS) calculation, digitalization training, and pitch deck preparation. Each session includes practical simulations, discussions, and Q&A to deepen participants' understanding. The results of the activity show a significant improvement in understanding, from a pre-test score of 39% to an 88% post-test score. This finding proves that experiential learning is effective in strengthening the practical skills of MSMEs. This program has a real impact on preparing MSMEs to be more adaptable, manage their finances well, utilize digital technology, and develop professional business presentation strategies.